STUDI PENGARUH VARIASI DEBIT TERHADAP PENURUNAN KONSENTRASI BOD,COD, dan TSS LIMBAH CAIR DOMESTIK BLACK WATER MENGGUNAKAN REAKTOR UASB (Studi Kasus: Kelurahan Gabahan, Semarang) - Widayanto Kurniawan Eko Yendi Atmaja (Jurnal Teknik Lingkungan, 2013)
Domestic wastewater from toilets is termed as fecal wastewater or "black water" with a high organic content. Domestic wastewater black water in Indonesia is still largely done by processing flows into the septic tank. UASB reactor has the ability to treat wastewater with high organic load and tolerant of shock loads. Therefore we need the existence of a study on the effectiveness of treatment of domestic wastewater using UASB. Characteristics of domestic wastewater from the black water test results in the Gabahan Village, Semarang has value 3000 mg COD / l, BOD 1218 mg / l, TSS 1800 mg / l, temperature of 27.03 º C, and pH 7.13. UASB reactor in this study using a continuous system.